(untitled) (Research, Society and Development, 2020)
The internalization of confirmed cases of COVID-19 in the state of Pernambuco has raised concerns among the population. Thus, it was analyzed the official data provided by the daily bulletins of the municipal health secretariats of the municipalities, in the period from 23/04/2020 to 06/25/2020, collected weekly and the objective was to adjust different non-linear models in the analysis of cases / 10 thousand inhabitants of COVID-19 in the Pernambuco municipalities of Lajedo, Bom Conselho and Garanhuns, in addition to checking the inflection point of the disease, the period that informs about the decrease in the evolution of cases. For the comparison between the models, the adjusted determination coefficient, mean absolute deviation and Akaike information criterion were used. The verification of the assumptions of the residues was carried out through the Shapiro-Wilk tests for normality, Durbin-Watson tests for independence and Breush-Pagan tests for homoscedasticity, the assumptions were met. The best adjustments were Von Bertalanffy for the municipalities of Garanhuns and Bom Conselho and Gompertz for the municipality of Lajedo, despite overestimating the number of cases in the asymptotic limit. In calculating the absolute growth rate (ACT) it was found that the inflection points of all models occurred within the period of 64 days after the start of the pandemic. However, it is not possible to make reliable predictions of when the numbers of confirmed cases will be minimized due to being in an initial stage of interiorization. However, these results can be important in controlling the spread, guiding the authorities and the population to preventive care.